Deadwood-Inhabiting Bacteria Show Adaptations to Changing Carbon and Nitrogen Availability During Decomposition - Tláskal, Vojtěch; Baldrian, Petr (Frontiers in Microbiology, 2021)
Deadwood decomposition is responsible for a significant amount of carbon (C) turnover in natural forests. While fresh deadwood contains mainly plant compounds and is extremely low in nitrogen (N), fungal biomass and N content increase during decomposition. Here, we examined 18 genome-sequenced bacterial strains representing the dominant deadwood taxa to assess their adaptations to C and N utilization in deadwood. Diverse gene sets for efficient decomposition of plant and fungal cell wall biopolymers were found in Acidobacteria, Bacteroidetes and Actinobacteria. In contrast to these groups, Alphaproteobacteria and Gammaproteobacteria contained fewer carbohydrate-active enzymes and depended either on low-molecular-mass C sources or on mycophagy. This group, however, showed rich gene complements for N2 fixation and for nitrate/nitrite reduction – key assimilatory and dissimilatory steps in the deadwood N cycle. We show that N2 fixers are able to obtain C independently from either plant biopolymers or fungal biomass. The succession of bacteria on decomposing deadwood reflects their ability to cope with the changing quality of C-containing compounds and increasing N content.